Effect of pitting defects on the buckling strength of thick-wall cylinder under axial compression - Wang, Huakun; Yu, Yang; Yu, Jianxing; Xu, Weipeng; Chen, Haicheng; Wang, Zhaoyu; Han, Mengxue (Construction & building materials, 2019)
•The effect of pits on the collapse pressure of cylinder under axial compression was experimental and numerical studied.•A novel shell model with pitting defects was proposed.•Realistic pits can be simulated based on the user defined Python program.•The distribution of pit affects the bucking mode hence govern the collapse pressure.•Volume loss is a good parameter to relate the collapse pressure and corrosion damage. This paper is aimed at assessing the effects of uniformly and randomly distributed pitting defects on the collapse pressure (FCO) of thick-wall cylinder under axial compression, which is exposed to the marine splash zone. The buckling performance of locally corroded cylinder was experimental and numerical studied. The experimental program involved seamless stainless steel tubes (316L) with different size of pitting defects, which were simulated by cylindrical hole. The pitting defects were introduced into the outside surface of cylinder by milling and drilling, and then the buckling strength of such structure was obtained experimentally. The profile of cylinder was examined in details using RA7320 Portable Arm Coordinate Measuring Machine (PACMM), and the measured data was analyzed carefully. A novel shell model was also established by a user defined Python program, where both uniformly and randomly distributed pits can be considered and the computational efficiency was highly improved. After calibrated with the experiment results, the model was used to carry out a systematic parametric study. It indicated that the radial imperfection and out-of-straightness as well as pitting defects (pitting size, perforated or un-perforated and distribution pattern) are key parameters governing the collapse pressure of such cylinder, and the maximum cross sectional area loss or volume loss are good parameter to correlate the collapse pressure and pitting damage. For engineering practice, the uniformly distributed pits model is better due to the convenience and conservative point of view, and the computational cost is also lower. However, the randomly distributed pitting model is more realistic, and some special collapse mode can only be observed when the random nature was taken into account.